2018
DOI: 10.3345/kjp.2018.61.3.71
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postnatal catch-up growth according to definitions of small for gestational age infants

Abstract: PurposeSmall for gestational age (SGA) is confusingly defined as birth weight (BW) either below 3rd percentile or 10th percentile for infants. This study aimed to compare postnatal catch-up growth between SGA groups according to different definitions.MethodsData of 129 infants born with BW below the 10th percentile and admitted to Korea University Anam Hospital and Ansan Hospital were retrospectively reviewed. Height and weight were measured at 6, 12, and 24 months. Results were compared between group A (BW: <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
(24 reference statements)
2
4
2
1
Order By: Relevance
“…31 Karlberg et al concluded that the vast majority (>86%) of 'healthy' full-term SGA infants will achieve ACUG already during the first 6-12 months of life, but about 50% remain short at (near) adult height. 11,32 In the present study, we also found that most children who achieve ACUG do so within the first 2 years of life (84.8% for height more than −2.5 SD and 80.5% for height more than −2 SD). This pattern may reflect the gradual diminishing effect of the intrauterine environment and the expression of the genetically programmed height.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…31 Karlberg et al concluded that the vast majority (>86%) of 'healthy' full-term SGA infants will achieve ACUG already during the first 6-12 months of life, but about 50% remain short at (near) adult height. 11,32 In the present study, we also found that most children who achieve ACUG do so within the first 2 years of life (84.8% for height more than −2.5 SD and 80.5% for height more than −2 SD). This pattern may reflect the gradual diminishing effect of the intrauterine environment and the expression of the genetically programmed height.…”
Section: Discussionsupporting
confidence: 76%
“…As to the rate of achieving ACUG, most previous studies reported only 85%‐90% of spontaneous ACUG in SGA infants during the first 2 years of life 31 . Karlberg et al concluded that the vast majority (>86%) of ‘healthy’ full‐term SGA infants will achieve ACUG already during the first 6‐12 months of life, but about 50% remain short at (near) adult height 11,32 . In the present study, we also found that most children who achieve ACUG do so within the first 2 years of life (84.8% for height more than −2.5 SD and 80.5% for height more than −2 SD).…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies have shown that CUG is not influenced by antenatal factors. 12,13 The association found in our study may be attributed to the severity of antenatal medical conditions and other confounding factors such as maternal age, pregnancy weight gain, or parity, although no significance was noted via multivariate analysis.…”
Section: Discussioncontrasting
confidence: 62%
“…This difference between studies might be due to different definitions. 26 Studies have used weight, body length, and head circumference for evaluation, with catch-up growth defined as an increase in the corresponding physical index Z scores by >0.67. 14 Full-term SGA infants tend to have rapid catch-up growth after birth.…”
Section: Discussionmentioning
confidence: 99%